Unmanned aerial vehicle storage mechanism and vehicle - REN RONG; WANG JUNQIANG; GAO XUEFENG; LIU XIONG; ZHU LIANGYI (2024)
The invention relates to an unmanned aerial vehicle storage mechanism and a vehicle, the unmanned aerial vehicle storage mechanism comprises a first platform, a second platform and a turnover mechanism, and the turnover mechanism is arranged between the first platform and the second platform. The driving device is arranged on the first platform and used for driving the second platform to be switched between a first position and a second position relative to the first platform, the first platform and the second platform are parallel to each other at the first position, and the first platform and the second platform are arranged in a mutually inclined or right-angle mode at the second position. According to the technical scheme, the unmanned aerial vehicle storage mechanism is small in size. 本公开涉及一种无人机收纳机构和车辆，所述无人机收纳机构包括第一平台、第二平台和翻转机构，所述翻转机构布置在所述第一平台和所述第二平台之间，并且用于驱动所述第二平台相对于所述第一平台在第一位置和第二位置之间切换，在所述第一位置，所述第一平台和所述第二平台相互平行，在所述第二位置，所述第一平台和所述第二平台相互倾斜或呈直角地布置。通过上述技术方案，本公开提供的无人机收纳机构体积较小。